Suppression of pro-inflammatory and proliferative pathways by diferuloylmethane (curcumin) and its analogues dibenzoylmethane, dibenzoylpropane, and dibenzylideneacetone: role of Michael acceptors and Michael donors - Anand, Preetha (2011)
Curcumin, a diferuloylmethane, has been shown to exhibit anti-inflammatory and anti-proliferative activities. Whereas curcumin has both a Michael acceptor and a Michael donor units, its analogues dibenzoylmethane (DBM, a component of licorice) and dibenzoylpropane (DBP) have a Michael donor but not a Michael acceptor unit, and the analogue dibenzylideneacetone (DBA) has a Michael acceptor unit. In the current report, we investigated the potency of DBM, DBP, and DBA in relation to curcumin for their ability to suppress TNF-induced NF-κB activation, NF-κB-regulated gene products, and cell proliferation. We found that all four agents were active in suppressing NF-κB activation; curcumin was most active and DBM was least active. When examined for its ability to inhibit the direct DNA binding activity of p65, a subunit of NF-κB, only DBP inhibited the binding. For inhibition of TNF-induced IKK activation, DBA was most active. For suppression of TNF-induced expression of NF-κB regulated gene products such as COX-2 (inflammation marker), cyclin D1 (proliferation marker), and VEGF (angiogenesis marker), DBA and curcumin were more active than DBM. Similarly for suppression of proliferation of leukemia (KBM-5), T cell leukemia (Jurkat), prostate (DU145), and breast (MDA-MB-231) cancer cells, curcumin and DBA were most active and DBP was least active. Overall, our results indicate that although curcumin and its analogues exhibit activities to suppress inflammatory pathways and cellular proliferation, a lack of Michael acceptor units in DBM and DBP can reduce their activities.